Sinopsis de las especies austro-americanas del género Nassella (Poaceae, Pooideae, Stipeae) - Cialdella, Ana Maria (2013)
Nassella is an American genus which, according to its current circumscription, includes about 116 species, distributed from Canada to Argentina and Chile. It is characterized by its florets with the lemma conspicuously convolute, with an apical conspicuous or inconspicuous crown, and the palea shorter than the lemma; furthermore, the lemma presents a distinctive epidermal pattern. The aim of this work is to provide a synopsis of the 99 species of Nassella which grow in southern South America, comprising Argentina, Bolivia, southern Brasil, Chile, Paraguay and Uruguay. A key to identify the species, mainly based on floret characters, is given. For each species, the current synonyms, geographic distribution, phenology, observations, and illustrations are presented. Nassella barbinodis is accepted and, Nassella linearifolia is a new synonym of Nassella caespitosa. Lectotypes are here designated for the following taxa: Danthonia nardoides, Piptochaetium collinum, P. gibbum, P. laevissimum, Stipa arechavaletae, S. barbinodis, S. breviculmis, S. calchaquia, S. carettei, S. clarazii var. bulbosa, S. curicoana, S. debilis var. papillosa, S. duriuscula, S. hispida, S. hyalina, S. julietii, S. longiglumis, S. macrathera, S. manicata var. media, S. mendocina, S. pratensis, S. pseudopampagrandensis, S. rupestris, S. tenuis, S. trachysperma, S. trichocaulos, and S. uspallatensis. A neotype is designated for S. filiculmis.